Advances in astrocytic calcium signaling research - Chen, Yuzhu; Ye, Yejun; Jia, Joyce; Long, Binhao; Dou, Tingting; Yan, Xingke (Frontiers in Cellular Neuroscience, 2025)
Astrocytes are the most abundant glial cells in the central nervous system. They detect neuronal activity through Ca2+ signals and thereby regulate synaptic plasticity, integrate neuronal information, and maintain extracellular homeostasis. Growing evidence indicates that aberrant astrocytic Ca2+ signaling is an important pathological factor in the onset and progression of many neurological disorders. In this review, we systematically summarize the sources, classifications, detection methods, and functional significance of astrocyte Ca2+ signaling, with the aim of improving understanding of astrocyte function and providing new perspectives and rationale for therapeutic strategies targeting related diseases.